Research on Autonomous Driving Path Planning Technology Based on Reinforcement Learning - Hao, Linfeng (Journal of Computer, Signal, and System Research, 2025)
Path planning is one of the key technical challenges in the field of autonomous driving. Thanks to the rapid advancement of reinforcement learning (RL) technology in the field of artificial intelligence, research on autonomous driving path planning based on RL is increasingly receiving attention. This study explores the use of reinforcement learning to implement autonomous driving path planning technology, analyzing the needs of multiple aspects such as environmental perception, model construction, obstacle avoidance, and path length optimization. A practical application scheme of reinforcement learning for path planning in different autonomous driving scenarios has been proposed. By comparing reinforcement learning algorithms such as DQN, A3C, PPO, etc., the adaptability and optimization ability of these algorithms in handling complex environments were explained, and the strategy of using multi-agent reinforcement learning for path planning was discussed.